Bacterial lipopolysaccharides form physically cross-linked, two-dimensional gels in the presence of divalent cations - Herrmann, Moritz; Schneck, Emanuel; Gutsmann, Thomas; Brandenburg, Klaus; Tanaka, Motomu (Soft matter, 2015)
We established a bacterial membrane model with monolayers of bacterial lipopolysaccharides (LPS Re and LPS Ra) and quantified their viscoelastic properties by using an interfacial stress rheometer coupled to a Langmuir film balance. LPS Re monolayers exhibited purely viscous behaviour in the absence of calcium ions, while the same monolayers underwent a viscous-to-elastic transition upon compression in the presence of Ca2+. Our results demonstrated for the first time that LPSs in bacterial outer membranes can form two-dimensional elastic networks in the presence of Ca2+. Different from LPS Re monolayers, the LPS Ra monolayers showed a very similar rheological transition both in the presence and absence of Ca2+, suggesting that longer saccharide chains can form 2D physical gels even in the absence of Ca2+. By exposure of the monolayers to the antimicrobial peptide protamine, we could directly monitor the differences in resistance of bacterial membranes according to the presence of calcium.